Longitudinal Association Between Birth Weight, Birth Length, and Linear Growth in Early Childhood - Sari Dwi Jayanti; Hanum Ferdian; Annang Giri Moelyo; Andhika Trisna Putra (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2026)
Background: Linear growth in early childhood is a vital indicator of health and largely determined by birth weight and length. The influence of birth size diminishes with age, yet the timing of this decline remains unclear in Indonesian children. This study aims to examine the influence of birth weight and birth length on linear growth among Indonesian children under five years of age and to determine the age at which these factors no longer play a significant role in body height. Subjects and Method: A retrospective cohort design was used, including a total of 2,287 children aged 0–60 months in Kayong Regency, West Kalimantan, Indonesia, by the year 2023-2024. Birth weight and length data were collected retrospectively from Child Health Books, and height-for-age z score (HAZ) was measured at the time of the study descriptive statistics were used to summarize the basic characteristics of the cohort. Results: The linear regression results demonstrated that both birth weight and birth length had a significant association with HAZ in 0-60 months of age. However, this association diminished markedly with age. The effect of birth weight and birth length on linear growth status (HAZ) is more objective statistical interpretation up to 30–36 months of age. These comparisons suggest that while the statistical influence of birth weight and birth length on HAZ diminishes around 30–36 months, the biological effects of early growth constraints may persist beyond this threshold, particularly in environments where nutritional recovery or healthcare access is limited. Conclusion: The influence of birth anthropometric, particularly birth weight and birth length, on children’s linear growth, measured by height-for-age Z-score (HAZ), is strongest during early life and gradually decreases with age.